Sociological studies of children and youth. - Rosier, Katherine Brown (JAI, 2003)
Two prominent themes of the volume are adolescents' transition to adulthood and children's time-use issues. Several chapters address each of these issues, including one examining children's labor in Senegal. Two ethnographic studies are included: one analyzes student-teacher interaction in an urban high-school math class, while the other examines friendship development and maintenance of early elementary-aged African American girls. The volume also includes a policy analysis of medical insurance provision for low income children, and a response to an earlier chapter on children's rights that appeared in Volume 8.